Leveraging luxury brands purchase intention through cultural congruent assertive advertising: A cross-cultural experimental evidence from Malaysia and Pakistan - Syed Hassan Raza; Umer Zaman (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Recently, scholars suggested that brands can leverage their sales by developing advertisements through identifying the particular cultural orientation associated with consumer behavior in question. However, little effort has been made in understanding this phenomenon that how presentation and message manifested with cultural orientation in luxury brand advertisement can provide better action cues to consumers. Henceforth, this study presents a hypothetical model by integrating assertiveness appeals that have been frequently used in luxury brands to compare their effectiveness across cultures. To that end, the study underscores the fundamental query that whether the usage of culturally congruent assertiveness in the advertisement is an effective strategy for luxury brand promotion in emerging markets. The study has employed a quasi-experimental survey using luxury brand advertisement manifesting assertiveness appeal. Data was collected from 340 individuals of Pakistan and Malaysia after exposure to ad stimuli. The findings of structural equation modeling using AMOS 24 validate the effectiveness of the assertive advertising appeal usage across both nations. This implies that using assertive presentation and message in luxury brands advertisement could leverage the buying behavior in emerging markets.
Keywords: 330; luxury brand; attitude towards luxury brands; assertive advertising; societallevel assertiveness; assertive appeal